Use of Aspergillus niger to landfill leachate treatment - Fakhru'l-Razi, Ahmadun; Alam, Md. Zahangir (2002)
The study of sanitary landfill leachate treatment by filamentous fungusi Aspergillus niger was conducted in a laboratory. The results presented in this study indicated that bioconversion of landfill leachate was highly influenced by the potential microbe A. niger. The higher production of dry biomass recorded was 14.2 g/L. The removal rate of COD, TSS and turbidity was observed with 86%, 96%, and 72% respectively after final days of treatment (9 days) compared to untreated sample (control). The effective results were received after 6 days of treatment. The fungal strain also affects the pH values in treatment and presented.